An ultra-compact all optical full adder based on nonlinear photonic crystal resonant cavities - Cheraghi, F.; Soroosh, M.; Akbarizadeh, G. (Superlattices and microstructures, 2018)
In this paper we are going to propose and design an all optical full adder based on photonic crystal. For realizing the proposed structure we will use four nonlinear resonant cavities inside a two dimensional photonic crystal. Nonlinear resonant cavities will be created by replacing the ordinary rods via defect rod made of nonlinear material such as doped glass. The simulation results show that the worst cases for logics 0 (the maximum normalized power in OFF state) and 1 (the minimum normalized power in ON state) are 3% and 53% for SUM port and they are 10% and 100% for CARRY port respectively. Also the maximum delay time for the proposed device is about 8 ps. •The proposed structure has very compact footprint compared with previously proposed full adders.•Delay time obtained to be about 8 ps so it's suitable for optical processing.•The light intensity required in input ports are lower than previously proposed structures.